PERSEPSI BAURAN PEMASARAN TERHADAP KEPUTUSAN PEN GGUN A AN KEMBALI JASA EKSPEDISI MUATAN KAPAL LAUT - ., Evianah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
The purpose of this of this research is to find out of marketing mixed perception on repurchase decision the EMKL companies. Analytical tool that the research employed was multiple linear regressions to know the effect of service users’ perception on the product, price, place, promotion, people, physical evidence, and process concerned with the repurchase decision the EMKL services. Hypotheses were verified by performing regression analysis (F-test) and partial testing (t-test). The result showed that the perception of service user on product, price, place, promotion, people, physical evidence, and process have significant effect on the repurchase decision. This could be seen from F-test of 10.884 larger than F table of 2.21. Thus, hypothesis starting that perception of the service users on product, price, place, promotion, people, physical evidence, and process had significant influence on repurchase decision the EMKL service was accepted.